Persepsi Konsumen Tentang Keamanan Data pada Aplikasi E-Wallet : Studi Kasus Dana - Devita Azwi Nurrahma; Nibi Nazwa Quinita Tanjung; Gema Surya Gemilang; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Data security is a crucial aspect in the use of digital wallet applications, especially in Indonesia where its implementation is increasing. This study aims to explore user perceptions of the level of data security in the DANA e-wallet application through a qualitative approach. Data were obtained through in-depth interviews with a number of active users, then analyzed thematically to identify factors that influence their sense of security in using the application. The results of the study show that transparency, privacy policies, ease of use of security features, and the reputation of service providers are important elements in building user trust. This study is expected to contribute to the development of data security management strategies in e-wallet applications in order to increase consumer satisfaction and loyalty.